Thallium and lead variations in a contaminated peatland: A combined isotopic study from a mining/smelting area - Vaněk, Aleš; Vejvodová, Kateřina; Mihaljevič, Martin; Ettler, Vojtěch; Trubač, Jakub; Vaňková, Maria; Goliáš, Viktor; Teper, Leslaw; Sutkowska, Katarzyna; Vokurková, Petra; Penížek, Vít; Zádorová, Tereza; et al. (Environmental pollution (Barking, Essex, 2021)
Vertical profiles of Tl, Pb and Zn concentrations and Tl and Pb isotopic ratios in a contaminated peatland/fen (Wolbrom, Poland) were studied to address questions regarding (i) potential long-term immobility of Tl in a peat profile, and (ii) a possible link in Tl isotopic signatures between a Tl source and a peat sample. Both prerequisites are required for using peatlands as archives of atmospheric Tl deposition and Tl isotopic ratios as a source proxy. We demonstrate that Tl is an immobile element in peat with a conservative pattern synonymous to that of Pb, and in contrast to Zn. However, the peat Tl record was more affected by geogenic source(s), as inferred from the calculated element enrichments. The finding further implies that Tl was largely absent from the pre-industrial emissions (>~250 years BP). The measured variations in Tl isotopic ratios in respective peat samples suggest a consistency with anthropogenic Tl (ε205Tl between ~ -3 and -4), as well as with background Tl isotopic values in the study area (ε205Tl between ~0 and -1), in line with detected 206Pb/207Pb ratios (1.16-1.19). Therefore, we propose that peatlands can be used for monitoring trends in Tl deposition and that Tl isotopic ratios can serve to distinguish its origin(s). However, given that the studied fen has a particularly complicated geochemistry (attributed to significant environmental changes in its history), it seems that ombrotrophic peatlands could be better suited for this type of Tl research.
Keywords: hornictví; Environmental Monitoring; Lead; Soil; Contamination; thallium; půda; Thallium; Isotopes; Deposition; Mobility; olovo; Peat; Mining; monitorování životního prostředí